Electron-lattice coupling in congruent co-doped LiNbO3:Cr3+:ZnO crystal - Torchia, Gustavo Adrián (2001)
The importance of the role of the ion lattice coupling in determining the energy levels of Cr³⁺ ions in congruent LiNbO3 crystals doped with 2.9% of ZnO is demonstrated in this paper. The Racah parameters: B 533 cm 1, C 3244 cm⁻¹ and the crystal-field intensity Dq = 1527 cm⁻¹ were determined and the Tanabe-Sugano diagram was constructed. The characteristics of the absorption and the emission spectra of Cr³⁺ ions in these crystals can be explained in terms of the configurational-coordinate diagram in the harmonic approximation, with good agreement obtained. The Huang Rhys parameter S 6.86 and the lattice phonon energy hw= 343 cm⁻¹ are also reported in this work